A Fuzzy AHP analysis of it outsourcing monitoring in public organizations - Ribeiro Felisoni, Paulo; Silva Martins, Fellipe; Librantz, Andre Felipe Henriques (Perspectivas em Gestão & Conhecimento, 2022)
Current literature on information technology points to a scenario where resistance to change must be considered in all IT implementation processes. However, there is no consistency in the extant literature about the interplay among the several triggers to resistance to change in IT. This paper aims at surveying the literature and investigating their roles in IT change management. Fuzzy AHP (Analytical Hierarchical Process) is used to provide greater flexibility in understanding the answers. The results point to two main sets of behaviours (intrinsic and extrinsic), which find support from other management fields. This paper contributes to the literature by showing that contrary to what was formerly believed, resistance to change in IT is not as much linked to technical aspects but to personal and team-level causes. As a methodological contribution a weighting scheme to fuzzy AHP is introduced, to cope with varying degrees of information across teams, in order to add an improvement in the method used, aiming at a better precision in the results.